Faktor-Faktor yang Berhubungan dengan Keberhasilan Pengobatan Pasien Kusta di Puskesmas Maubesi - Melania Oeleu; Sigit Purnawan; Amelya B. Sir (Media Kesehatan Masyarakat, 2022)
Treatment of leprosy sufferers aims to break the chain of leprosy transmission. The success of leprosy treatment depends on early detections of the patient, adherence to medication, community stigma and the role of health workers. The purpose of this study was to examine the relationship between medication adherence, community stigma and the role of health workers in the successful treatment of leprosy patients at the Maubesi Public Health Center, North Central Timor Regency, in 2019. This research is a qualitative research. The research informants were 13 people consisting of 5 key informants and 8 supporting informants. Data processing and analysis techniques use thematic analysis. The results of the research at Maubesi Public Health Center show that the informants comply with every rule of leprosy treatment management, both short term for PB leprosy and long term for MB leprosy. Although there is a stigma and negative treatment from the community towards people with leprosy, such as the assumption that leprosy cannot be curred and the community is afraid to shake hands with people with leprosy, it does not interfere with the patient to be afraid and retreat in undergoing leprosy treatment. This is supported by the role of health workers in the discovery and treatment of leprosy patients. Patients with good support from health workers are more obedient in taking treatment. Suggestion for the Health Center to increase education about leprosy to reduce stigma in the community.